Community and Local Governance in Australia - Paul Smyth, Tim Reddel and Andrew Jones (A UNSW Press book, 2005)
The contributions collected in this volume result from an Australian Research Council project initiated in 2001 by the School of Social Work and Applied Human Sciences of the University of Queensland in collaboration with the Queensland Government departments of the Premier and Cabinet, and Families. The research project was initiated because of the editors’ interest in examining the upsurge of spatially based policy activity aimed at addressing the spatial disadvantage that occurred in Queensland in the latter 1990s. The project’s examination over three years of the Queensland experience also highlighted similar policy initiatives in other Australian States. These developments mirrored global trends. Globalisation has accentuated uneven regional economic development, and governments throughout the world are seeking new policy directions to address the needs of people and communities excluded from the benefits and opportunities of citizenship by virtue of where they live.